Analisis Pola Curah Hujan Terhadap Produktifitas Tanaman Padi Sawah di Provinsi Jawa Barat - Faradiba (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2020)
Increasing agricultural productivity can be influenced by various factors, one of which is rainfall. Changes in rainfall that are quite volatile cause agricultural productivity, especially for wetland paddy, is difficult to predict. The importance of predictions is made in order to prevent the decline in productivity of paddy that have an impact on the welfare of the people in Indonesia. This study aims to look at changes in rainfall patterns associated with the productivity of wetland paddy. The data used in this study is in the form of rainfall and wetland paddy production in 2002-2015. The method u`sed in this research is descriptive analysis related to pattern analysis and determination of data patterns using spectral analysis which can be seen from the results of peroidigrams. The results of this study are the pattern of rainfall that is repeated based on the periodogram analysis. Rainfall patterns in West Java Province occur every 33 months or 3 years. Increased productivity of wetland paddy occurred in 2006, 2009,2012, 2015 in accordance with the pattern of rainfall that occurs every 3 years. The characteristics of rainfall types in West Java Province in 2002-2015 are in the range of slightly wet to very wet. Keywords : rainfall, wetland paddy,spectral analysis.